2011
DOI: 10.1002/jmr.1098
|View full text |Cite
|
Sign up to set email alerts
|

Receptor‐attached amphiphilic terpolymer for selective drug recognition in aqueous solutions

Abstract: In the present work, a combination of binding studies and molecular docking were employed to demonstrate drug encapsulation and host-guest chemistry in self-assembled micelles consisting of amphiphilic terpolymers. The terpolymer is composed of poly(3-sulfopropyl methacrylate), as the hydrophilic component, poly(n-dodecyl acrylate), as the hydrophobic component and poly(barbiturate receptor), as the component for drug recognition. The combined approach was tested on four model compounds from the family of barb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 53 publications
(52 reference statements)
0
8
0
Order By: Relevance
“…Incorporation of a specific receptor into a polymer backbone was demonstrated by Loizidou and co-workers wherein a barbiturate receptor was designed and synthesized ( figure 10 a ) [ 77 ]. Barbiturates are central nervous system depressants and exhibit both hydrogen-bond donor (amine) and acceptor (carbonyl) sites, depending on the specific barbiturate molecule ( figure 10 b ).…”
Section: Recognition Of Small Molecules By Polymer Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Incorporation of a specific receptor into a polymer backbone was demonstrated by Loizidou and co-workers wherein a barbiturate receptor was designed and synthesized ( figure 10 a ) [ 77 ]. Barbiturates are central nervous system depressants and exhibit both hydrogen-bond donor (amine) and acceptor (carbonyl) sites, depending on the specific barbiturate molecule ( figure 10 b ).…”
Section: Recognition Of Small Molecules By Polymer Materialsmentioning
confidence: 99%
“…The recognition ability of the polymer was tested in aqueous solutions of four barbiturates that comprise different numbers of hydrogen-bonding sites. Binding constants ranging from 10 2 to 10 5 M −1 were realized in solution, and computational studies revealed that a combination of hydrogen bonding and binding geometry contribute to the recognition ( figure 10 c ) [ 77 ].
Figure 10.
…”
Section: Recognition Of Small Molecules By Polymer Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…A c c e p t e d M a n u s c r i p t 15 In order to calculate the MOF-surfactant binding constant, a more quantitative approach is provided by the following modified form of Benesi-Hildebrand relation [48,[64][65][66];…”
Section: Partition Constant and Gibbs Energy Changesmentioning
confidence: 99%
“…These interactions deemed to play an important role in developing targetspecific drugs and drug delivery systems [12][13][14][15]. The physical behavior of the surfactant micelles can considered as the configuration of pseudo-model of biological membranes to mimic a biological system.…”
Section: Page 5 Of 25mentioning
confidence: 99%